Pembentukan Karakter Religius Melalui Kegiatan Pembiasaan Pada Siswa di SDN 4 Baosan Kidul Ponorogo - Linda Nur Ayudia; Afif Syaiful Mahmudin (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
Until now, children still behave in ways that are not in accordance with Islamic teachings, such as cheating, smoking, dating or bullying. This research aims to: (1) analyze the habituation activities carried out by teachers in forming religious character in students, and (2) analyze the impact of habituation activities carried out by teachers in forming religious character in students. The method used is a qualitative method. The results of this research: (1) habituation activities carried out by teachers: (a) 3S, (b) praying, (c) reading the Qur'an/iqra', (d) Dhuha prayer, (e) Dhuhur prayer, (f ) clean living and (g) PHBI, (2) the impact of these habituation activities is the development of moral values, tolerance, emotional well-being, academic motivation and positive interpersonal relationships, (3) supporting and inhibiting factors. The supporting factors for the formation of religious character through habituation activities are first, teacher competence. whatsapp group. Meanwhile, the inhibiting factors in character formation through habituation activities are family factors, peer factors, and gadget factors.